2012
DOI: 10.1007/s10903-012-9679-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Living Arrangements on the Management and Control of Hypertension: A Mixed-Methods Study of Korean American Elderly

Abstract: Elders living alone may experience worse health outcomes than do those living with spouse and/or children. Using baseline data from a randomized trial to promote high blood pressure (HBP) control in Korean elders (N=440), we examined the relationship between living arrangements and HBP control. We also interviewed a sub-sample to better understand the patterns of social interactions associated with different types of living arrangements. One in five reported living alone; this group tended to be older and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…Consistent with prior studies, in the present study, the degree of self‐esteem was associated with the level of happiness, despite the fact that participants were living alone. Self‐esteem has been found to be related to the size of the social network, and older women might be particularly sensitive to social support . The older women living alone in the present study participated in social activities, such as dancing or cooking, and this helped them retain their self‐esteem.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Consistent with prior studies, in the present study, the degree of self‐esteem was associated with the level of happiness, despite the fact that participants were living alone. Self‐esteem has been found to be related to the size of the social network, and older women might be particularly sensitive to social support . The older women living alone in the present study participated in social activities, such as dancing or cooking, and this helped them retain their self‐esteem.…”
Section: Discussionmentioning
confidence: 85%
“…However, these results were not always consistent. For example, in recent studies, the mental health and vitality of women living alone was found to be better than that of individuals living with their spouses . Similarly, it is meaningful to understand that older women living alone in South Korea have a moderate level of happiness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations